Crystal structure of 2-(3,5,5-trimethylcyclohex-2-en-1-ylidene)malononitrile, C12H14N2 - Liu Yingfan; Wang Mengfei (Zeitschrift für Kristallographie - New Crystal Structures)
C12H14N2, monoclinic, P21/c (no. 14), a = 10.16290(10) Å, b = 8.25800(10) Å, c = 13.4328(2), β = 95.910(1)∘, V = 1121.36(2) Å3, Z = 4, Rgt(F) = 0.0380, wRref(F2) = 0.1126, T = 294 K.